2021
DOI: 10.1007/s10753-021-01568-y
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulators of Inflammation Response to the Dynamic Expression of Cytokines in DF-1 and MDCK Cells Infected by Avian Influenza Viruses

Abstract: The H5N1 and H9N2 avian in uenza viruses (AIVs) seriously endanger the poultry industry and threaten human health. Characteristic in ammatory responses caused by H5N1 and H9N2 AIVs in birds and mammals result in unique clinical manifestations. The role of anti-in ammatory regulators, PTX3, Del-1 and GDF-15, in H5N1 and H9N2-AIV-mediated in ammation in birds and mammals has not yet been veri ed. Here, the expression of PTX3, Del-1 and GDF-15 in DF-1 and MDCK cells infected with H5N1 and H9N2 AIVs and their effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Interestingly, the GDF15 is highly expressed in males as compared to females as it is inversely correlated with testosterone level [ 29 ]. Recently, overexpression of anti-inflammatory GDF15 has been found to reduce the infectivity and severity of H5N1 [ 30 ]. Despite the GDF15 role in both viral and bacterial infections, it induces a protective effect by inducing metabolic tolerance against infection-induced inflammation [ 31 ].…”
Section: Growth Differentiation Factor 15 and Viral Infectionsmentioning
confidence: 99%
“…Interestingly, the GDF15 is highly expressed in males as compared to females as it is inversely correlated with testosterone level [ 29 ]. Recently, overexpression of anti-inflammatory GDF15 has been found to reduce the infectivity and severity of H5N1 [ 30 ]. Despite the GDF15 role in both viral and bacterial infections, it induces a protective effect by inducing metabolic tolerance against infection-induced inflammation [ 31 ].…”
Section: Growth Differentiation Factor 15 and Viral Infectionsmentioning
confidence: 99%
“…One recent paper demonstrated that GDF-15 overproduction increases severity of human rhinovirus infections ( Wu et al, 2017 ), and Kleinertz et al reported that GDF-15 levels were increased in injury patients who progressed to sepsis compared to those who did not ( Kleinertz et al, 2019 ). Likewise, GDF-15 expression is increased in cells infected with avian influenza viruses, and this in turn limits their production of cytokines ( Zhao et al, 2021 ). COVID-19 patients have elevated GDF-15 levels ( Notz et al, 2020 ; Rochette et al, 2021 ), suggesting a potential link between GDF-15 and disease severity in the ongoing pandemic.…”
Section: Gdf-15 and Immunitymentioning
confidence: 99%